The politics of imprisonment: how the democratic process shapes the way America punishes offenders - Barker, Vanessa (Studies in crime and public policy, 2009)
'The Politics of Imprisonment' examines how the democratic process and social trust shape penal sanctioning in the United States. Drawing on a range of archival sources, Barker shows that higher levels of civic engagement tend to support milder punishments whereas lower levels tend to support more coercive criminal justice policies.